Teachers' Use Of Oral Corrective Feedback During Grammar Classes At SMPN 189 - Maulida, Windy Jilan; Arianti, Theresia (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
Feedback given by the teachers are constantly required for their students to grow and learn. Oral corrective feedback is an essential part of the language development process. The aims of this study are to discover what types of errors that English teachers prefer to provide feedback on, to find out what type of oral corrective feedback is mostly used in the classroom, and to find out teacher's reason of preferred type of oral corrective feedback that is used in the classroom. This study helped the students be aware of their errors during reading classes and helped the teacher discover the appropriate types of oral corrective feedback for their students. This study employed a case study as a method and a qualitative descriptive approach. The most frequent errors made by students were morpho-syntactic errors. Feedback types mostly used in the grammar class were Recast and Elicitation Request. It is suggested that future studies conduct the same research but with written corrective feedback.